Flexural and Compressive Strength on No-fines Concrete Slab using Variations of Fly Ash and Superplasticizer - Monika, Fanny (International Journal of Integrated Engineering, 2019)
Concrete is one of the most used construction materials in the world. The advantages of concrete, which has a cheap and easily obtainable price, make this material popular in the world community. Concrete construction is usually used for building construction, bridges and rigid pavements on roads. This research will make concrete slabs without the use of fine aggregates which are often referred to as no-fines concrete. The reduction of the constituent material in the concrete causes the formation of cavities which aim to accelerate the absorption of water for road construction. The specimens were made in the size of 400 x 100 x 600 mm with three variations using fly ash and three variations using materials added superplasticizer and one variation without using any added material with a total of 21 samples. In addition to flexural testing, compressive strength testing was also carried out by making 63 cylindrical concrete samples measuring 150 mm in diameter and 300 mm in height. The flexural test is done when the concrete slab is 28 days old using a centralized static load in the middle of the span, while the concrete cylinder compressive strength test is carried out at the age of 7, 14 and 28 days.